Diversidade genética da abelha sem ferrão melipona quinquefasciata baseada no sequênciamento das regiões its1 e 18s do dna ribossômico nuclear - Pereira, Júlio Otávio Portela (2006)
The research was carried out from January 2003 to March 2006, at the Department of Animal Science and Department of Biology in the Federal University of Ceará, in Fortaleza, Ceará. Bee samples were collected in the states of Ceará, Piauí and Goiás, Brazil. The objective of this work was to study the genetic variability of populations of the stingless bee Melipona quinquefasciata, which occurs naturally in the plateau of Araripe (South of Ceará), in the plateau of Ibiapaba (West of Ceará), in Canto do Burití, Piauí and Luziânia-Goiás (Center-Western, Brazil). Our aims were to contribute to the correct taxonomic classification of the Northeastern population and to give initial support to future work on the rational breeding of this species. Meliponiculture in rational hives for honey production will stimulate the change of the present predatory actions into a productive bee rearing activity which is ecologically sustainable. The regions of nuclear ribosomal DNA 18S and partial ITS-1 were extracted and sequenced and the following aspects were determined: nucleotid composition, matrixes of genetic distances, multiple alignments and cladograms. Results showed a high degree of similarity among the samples: 0,008 to region 18S, and 0,015 to partial ITS-1. The sequences’ size found to region 18S varied: from 1823 to 1869, and to ITS-1 from 491 to 572. The cladogram made to 18S presented a single clade. However, when external samples (M. quadrifasciata, M. subnitida, M. scutellaris, M. mandaçaia), were added to ITS-1, three groups were formed reflecting the described subgenus by the morphological taxonomy. Distance among the localities where samples were colleted was not significantly correlated to the dissimilarity of the bees to 17 18S. Nevertheless, there was a correlation with partial ITS-1, which contained the Piauí sample. Our conclusions are: (i) the bee samples from Ceará and Piauí cannot be distinguished, in molecular terms, from the bee samples of Goiás, suggesting they are the same species, although presenting some level of variability among the populations; (ii) the results reflect the taxonomy based in morphological aspects for Melipona quinquefasciata; (iii) the geographical distance suggested some level of alteration in the genoma of bees which inhabit in the three studied regions; (iv) the region partial ITS-1 of the nuclear ribosomal DNA, even in small bee samples, can help to solve taxonomic doubts at the subgenus level, in Melipona.